2022
DOI: 10.1101/2022.02.22.22271322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of the Weight Self-Stigma Questionnaire (WSSQ) in Subjects with Overweight and Obesity living in Italy

Abstract: Aims: Although weight-based stigmatization is widespread in everyday life, a suitable measure of weight self-stigma is currently unavailable for those with overweight/obesity whose primary language is Italian. The purpose of this study was to translate and test the psychometric properties of the Italian version of the Weight Self-stigma Questionnaire (I-WSSQ) to administer it to adults with overweight/obesity. Materials and Methods: A cross-sectional study was conducted on 214 adults with overweight or obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…78 secondary institutions (Maïano et al 2019). However, they reported that in a different cross-sectional study done on 214 Italian people who were overweight or obese, a significant relationship between the WSSQ subscales and body mass index was discovered (Liviaa et al 2022).…”
Section: )mentioning
confidence: 97%
“…78 secondary institutions (Maïano et al 2019). However, they reported that in a different cross-sectional study done on 214 Italian people who were overweight or obese, a significant relationship between the WSSQ subscales and body mass index was discovered (Liviaa et al 2022).…”
Section: )mentioning
confidence: 97%
“…I fascicoli sono due, entrambi precedenti: il primo è degli anni 1586-1594; gli imputati per magia sono nove: sette uomini (Giovan Battista Attenasio, Marco Antonio Avogadro, Ettore Cangiano, Giovan Vincenzo Carbone, Andrea Coccia, Cesare Manso, Cirillo Riccio) e due donne (Antonia Lombarda e Faustina Vulcana). 2 Il secondo processo è degli anni 1586-1588; gli imputati per magia sono otto: due uomini (Francesco Acquarese, Giovan Battista Caracciolo) e sei donne (Argenta Amorosa, Beatrice Castiglione, Grandizia de Criscienzo, Ippolita Palomba, 3 Silvia Telesa, Faustina Vulcana). 4 Rileviamo che non sono poche le persone coinvolte nei due processi, uomini e donne, ma nessuna che abbia preso i voti; colpisce un cognome di notevole rilievo, come Caracciolo, e solo Faustina Vulcana è presente in entrambi i procedimenti.…”
Section: Napoli: Suor Vittoria Vulcanaunclassified